The diseases of putative occupational origin reported and analysed in the Malprof Surveillance System - Campo, Giuseppe; Pizzuti, Antonio; Curti, Stefania; Mattioli, Stefano; Baldasseroni, Alberto; Di Leone, Giorgio; Magna, Battista; Leva, Antonio; De Santis, Daniele; Cosimi, Fabio; Montanari, Paolo; Papale, Adriano (La Medicina del Lavoro, 2018)
The Malprof (MALattie PROFessionali) surveillance system records data on work-related diseases collected by the sub-regional Departments of Prevention of the Italian National Health Service. The archive classifies diseases according to the occupational sector and the professional activity, allowing data analyses regarding the work-related causes of the diseases. In the Malprof system the occupational physicians of sub-regional Departments of Prevention attribute a causal link between disease and occupational sector/job title, following a preliminary evaluation of the data regarding the completeness of the occupational history and the quality of the diagnosis. The cases recorded between 1999 and 2014 amount to about 160,000. The general analysis by type of disease confirms that musculo-skeletal disorders are the most common work-related disease, accounting for 67% of the cases. As indicator of the strength of the association between disease and activity sector, the prevalence ratio (PR or prevalence rate ratio, PRR) was used. An example is the one related to the association between leather working sector and seno-nasal neoplasms which had a PRR point estimate of 33.1. Apart from analyses regarding putative occupational diseases, the Malprof system permits to plan targeted preventive interventions and the evaluation of their effectiveness.